HARMONI KEUTUHAN BUDAYA MASYARAKAT BADUY DALAM MENYINGKAP PERKEMBANGAN PENDIDIKAN - Suaidi Suaidi (Journal of Student Research, 2024)
Education and human life cannot be separated, because education as a determinant of the direction of human life, the higher human education will show the higher quality of human life and vice versa. In line with the development of education, however, there are still people who reject the progress of education because they believe that the development of the times is not a guarantee for the realization of independence and peace of mind. This research aims to raise the issue of education development in Baduy community of Leuwidamar District, Lebak Regency, Banten Province. The Baduy community consists of groups, Inner Baduy, Outer Baduy and Muallaf Baduy, the three of them have their own uniqueness, for the Inner Baduy community they reject various forms of modernization, while the Outer Baduy community they accept although there is still a classification between what is accepted and what is rejected, while the Muallaf Baduy community totally accepts the development even their lifestyle is not like the lifestyle of urban communities, in terms of their children's education some of them have enjoyed higher education.